Education in Designing out Crime - A Case Study - Cozens, Paul (Design Out Crime Research Centre, 2009)
The State's Designing Out Crime Strategy (Office of Crime Prevention, 2007) is committed to reducing opportunities for crime and the fear of crime using Designing Out Crime principles and strategies. One of its five goals is to increase / disseminate understanding of Designing Out Crime.This phenomenological case study discusses the development of Designing Out Crime education within Curtin University of Technology's Urban and Regional Planning Department and the dissemination of Designing Out Crime ideas to planning students. Insights on students' knowledge and interest in Designing Out Crime were gathered from a series of urban and regional planning field trips, lectures to students from product design, interior architecture, architecture, urban design and urban and regional planning and the supervision of numerous undergraduate planning dissertations on Designing Out Crime. Along with ongoing research into the Designing Out Crime field, insights from this research and teaching experiences are being synthesised to develop more critical teaching programs for Designing Out Crime. The knowledge is currently being formulated into a textbook, which will form the basis for a Special Projects Unit, representing an elective unit for undergraduate students in Urban and Regional Planning.Keywords: designing out crime, crime prevention through environmental design (CPTED), education, teaching, research, urban and regional planning.